2009
DOI: 10.4314/ajbr.v10i1.48917
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of food security status of rural households living with HIV/AIDS in southwestern Nigeria

Abstract: The study assessed the determinants of food security status of households living with HIV/AIDS in Southwestern Nigeria. Eighty-five people living with HIV/AIDS were interviewed for the study. Descriptive statistics, cost of calorie measure and the Logit model were used in analyzing the data collected. The result shows that there is high prevalence of food insecurity among the households living with HIV/AIDS. The result of the Logit model also shows that gender, education, monthly food intake (Kcal), total mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Also as age increases, other factors such as farm experience may influence the food security status of households. Negative correlation between age squared and food security was revealed in the findings of Adenegan and Adewusi (2007).The positive effect of age and a negative effect of age squared imply as people get older the effect of age is lessoned. A positive effect of age and a positive effect of age squared means that as people get older the effect is age stronger.…”
Section: Sample Size and Sampling Techniques A Multistage Sampling Technique Was Usedmentioning
confidence: 92%
See 1 more Smart Citation
“…Also as age increases, other factors such as farm experience may influence the food security status of households. Negative correlation between age squared and food security was revealed in the findings of Adenegan and Adewusi (2007).The positive effect of age and a negative effect of age squared imply as people get older the effect of age is lessoned. A positive effect of age and a positive effect of age squared means that as people get older the effect is age stronger.…”
Section: Sample Size and Sampling Techniques A Multistage Sampling Technique Was Usedmentioning
confidence: 92%
“…Oluyole et al, (2009), examined the food security status among cocoa farming households of Ondo State, Nigeria and employed Cost-of Calorie (COC) function proposed by Greer and Thorbecke (1986). This method was also used in similar studies (Ojogho, 2010;Adenegan and Adewusi, 2007). The function is stated as:…”
Section: Methodsmentioning
confidence: 99%
“…While in rural Ghana the poor food insecurity status is due to a number of factors: poor biophysical conditions, skewed distribution of wealth, low social capital and few opportunities for local non-farm activities. [32][33][34] Another study in rural Nigeria showed that about one third of the rural farming households sampled was food insecure and that farm size of the households, gross farm income, total non-farm income and household size are the significant determinants of rural household food security in the study area. Traditionally, in rural Burkina Faso, livestock rearing is one of the most important strategies used by households in agro-pastoral food production systems to improve their incomes as well as their food security.…”
Section: Causes Of Food Insecurity and Factors Associated With Itmentioning
confidence: 99%
“…Similarly studies in rural Nigeria, Amhara and Southern Ethiopia supports that farm income influences negatively household food insecurity. [26,32] In the study area people derive income from multiple sources-both from farm and non-farm sources. The sources of these incomes are off-farm activity, income from crop production, and income from livestock sell.…”
Section: Factors Associated With Household Food Insecuritymentioning
confidence: 99%
See 1 more Smart Citation